International Law Milestones Throughout History: Forming the Idea of Modern Sovereignty - Riadhotul Muamalah (Aktivisme: Jurnal Ilmu Pendidikan, Politik dan Sosial Indonesia, 2025)
This paper examines the evolution of international law from its early foundations to its contemporary form. Starting with the basic legal principles, it highlights significant milestones, such as the Peace of Westphalia in 1648, which established the concept of state sovereignty. The study also explores the contributions of Hugo Grotius, who is often regarded as the "Father of International Law," whose work significantly shaped the modern legal framework that governs relations between states. In addition, he analyzed the development of global institutions such as the United Nations, which emerged after World War II and played a crucial role in encouraging international cooperation and advancing international law in the 20th century. Particular attention is paid to treaty law, emphasizing how treaties between countries are important for maintaining global order. Using a qualitative research approach, this study provides a comprehensive understanding of historical and contemporary shifts in international law. It discusses how countries have balanced their sovereignty by pursuing global cooperation and broader peace. These findings underscore important moments in the evolution of international law, offering insights into the ongoing challenges and opportunities for global governance in the modern era.